Nutritional Strategies for Maintaining Optimal Hemoglobin Levels in Soccer Players: A Review of Health Implications - Indra Adi Budiman; Yovhandra Ockta (Jurnal Penelitian Pendidikan IPA, 2024)
This study uses a literature review-based qualitative descriptive research model to explore nutritional strategies in maintaining optimal hemoglobin levels in football players. The research process begins with the collection of literature from reliable sources, by accessing scientific databases such as Scopus, Science Direct, and Google Scholar using keywords such as "Nutrition Strategies," "Hemoglobin Levels," and "Soccer Players." After gathering the relevant literature, the authors reviewed important terms related to hemoglobin and their application to football players. Furthermore, data from the relevant literature is collected and analyzed. The data includes the author's name, year of publication, research design, research objectives, samples, instruments, and a summary of the findings. Articles that met the criteria were then filtered for further analysis. The documentation method is used to collect data by searching and extracting information from related literature. The collected data is then compiled into a comprehensive document to answer the research questions. Content analysis was conducted to evaluate the relevance and contribution of the study to nutritional strategies in maintaining hemoglobin levels. The conclusions of this analysis provide evidence-based recommendations regarding effective nutrition strategies to maintain optimal hemoglobin levels in soccer players.